Numerical modelling to evaluate temperature profile along an injection or production wellbore - Tarom, Nematollah (Curtin University, 2013)
This study developed numerical model to predict the flowing wellbore temperature profile (FWTP) of injection/production well for single and multiphase flow. A computer simulator, named WTP was developed employing this model. Case studies and sensitivity results demonstrated that: the simulator can be used as a powerful tool to analyse FWTP; and the behaviour and nature of dependency of FWTP is very complex. Such behaviour can be further influenced by many fluid and well related parameters.